Assessing future vent opening locations at the Somma‐Vesuvio volcanic complex: 2. Probability maps of the caldera for a future Plinian/sub‐Plinian event with uncertainty quantification. Issue 6 (17th June 2017) - Tadini, A.; Bevilacqua, A.; Neri, A.; Cioni, R.; Aspinall, W. P.; Bisson, M.; Isaia, R.; Mazzarini, F.; Valentine, G. A.; Vitale, S.; Baxter, P. J.; Bertagnini, A.; et al.
Abstract: In this study, we combine reconstructions of volcanological data sets and inputs from a structured expert judgment to produce a first long‐term probability map for vent opening location for the next Plinian or sub‐Plinian eruption of Somma‐Vesuvio. In the past, the volcano has exhibited significant spatial variability in vent location; this can exert a significant control on where hazards materialize (particularly of pyroclastic density currents). The new vent opening probability mapping has been performed through (i) development of spatial probability density maps with Gaussian kernel functions for different data sets and (ii) weighted linear combination of these spatial density maps. The epistemic uncertainties affecting these data sets were quantified explicitly with expert judgments and implemented following a doubly stochastic approach. Various elicitation pooling metrics and subgroupings of experts and target questions were tested to evaluate the robustness of outcomes. Our findings indicate that (a) Somma‐Vesuvio vent opening probabilities are distributed inside the whole caldera, with a peak corresponding to the area of the present crater, but with more than 50% probability that the next vent could open elsewhere within the caldera; (b) there is a mean probability of about 30% that the next vent will open west of the present edifice; (c) there is a mean probability of about 9.5% that the next medium‐large eruption will enlarge the present Somma‐Vesuvio caldera, and (d) there is a nonnegligible probability (mean value of 6–10%) that the next Plinian or sub‐Plinian eruption will have its initial vent opening outside the present Somma‐Vesuvio caldera. Key Points: New vent opening probability maps for a future Plinian/sub‐Plinian eruption of Somma‐Vesuvio volcano are developed The maps incorporate uncertainty estimates and uniquely include the special case of Somma‐Vesuvio caldera enlargement New volcanological/structural data sets (from the companion paper) are combined to create spatial probability density functions